LAGU SETIA JANJIKU: BENTUK PEMBARUAN MUSIK KERONCONG GAYA ISMANTO - Soladi, Soladi; Mintargo, Wisnu; Kiswanto, Kiswanto (Institut Seni Indonesia (ISI) Surakarta, 2020)
Songs that develop in keroncong music have been classified strictly based on their form, including the keroncong asli, langgam, stambul, and several other forms. The classification has become a very chain rule, as a result the creativity that emerges among keroncong musicians is often considered to be incompatible with the standards or parameters aesthetic of keroncong music by most keroncong music performers. These conditions do not always limit the composers and / or creators of keroncong songs to be creative in producing new products with different styles. One of them can be found in Ismanto's artworks around the 1960s. In one of his songs entitled Keroncong Setia Janjiku, Ismanto seems to have hit the boundaries that have been applied, but has a novelty with a strong character. The findings of this study indicate that the Song Setia Janjiku is a song keroncong asli that nglanggami.